Usable thoughts : climate, water and weather in the twenty-first century - Glantz, Michael H. (United Nations University Press, 2010)
Drawing upon a series of quotations taken from the World Meteorological Organization-sponsored publication, "Climate: Into the 21st Century," the authors of this publication set out to encourage thought and discussion on the earth's climate system, including its interrelatedness to human society and the environment, the impact of climate variability, and climate extremes and change.--Publisher's description